Raimunda and her women family in Volver de Pedro Almodóvar - Simonetti, Rafael Pereira (2016)
This analysis finds in the movie Volver, of Pedro Almodóvar, the problematic relation with conceptions of family in an occidental culture and of genders papers assigned socially to individuals that are part of it. Approaching themes that are present in the society and that escape the rules established through dialogue between family and society, the movie reveals things in common between fiction and critical about the existence of perverse realities. Domestic violence, sexual abuse, incest and pedophilia are themes that are present in the movie, and fall in the discussions made by thinkers of human science, like Joan Scott, Carole Pateman, Pierre Bourdieu, PhillipeAriès and William Goode. Illuminating questions about problems that are in familiarizes relations, the critical that are results of theoretical contributions have as focused on woman’s place in the family, analyzing specifically the one composed by woman characters of Volver.